Implementasi Gerakan Furudhul Ainiyah (GEFA) dalam Membentuk Karakter Anak Usia Dini di RA An-Nur Keras Diwek Jombang - Maulidatul Hidayati; Nur 'Azah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Character development from an early age is crucial, as this period is a golden age where children easily imitate. Educational institutions, such as RA An-Nur Keras Diwek Jombang, have implemented the Furudhul Ainiyah Movement (GEFA) program to support the character formation of young children. This study focuses on examining the implementation, evaluation, as well as the supporting and inhibiting factors of GEFA at the institution. The research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that GEFA was implemented through careful planning and scheduled execution, both inside and outside the classroom. Evaluation was conducted in the classroom and at the madrasah through observation and evaluation meetings. The supporting factors include adequate facilities, experienced teachers, as well as support from parents and a religious environment. The inhibiting factors include the pandemic, which led to Home Learning (BDR), and damaged supporting facilities such as the sound system.